Government and Cinema in France: How to Stand Up against American Cinema - Hojatollah Ayoobi (Taḥqīqāt-i Farhangī-i Īrān, 2008)
Cinema is the most influential cultural instrument in the contemporary world. The seventh art first brought culture in theaters and then in homes by T.V. and modern audio – visual devices. Perhaps, for this reason, André Marlow paid special attention to the cinema and regarded it as a shortcut to the popularization of culture or achieving cultural democracy. Since its birth, cinema in France experienced a significant progress and was the best before the Second World War. But with the entrance of Americans to this field, relying upon their modern technology and huge investments made considerable progress and challenged the French cinema. The French cinema needed government, help in this unequal competition and could not resist this all – out invasion on its own. The French government got involved in the sector of cinema to reach two goals: helping cultural and artistic cinema: and standing up against American cinema to defend the cultural diversity championed by the French. This article examines approaches results from a problem which is also considered a major concern for Iranian cinema. Relationship between government and cinema in France might absorb the attentions of our cultural policymakers.